The Current and Future Landscape of the Childhood Myopia Epidemic in China—A Review - Wei Pan; Weizhong Lan (Ophthalmology and Therapy, 2024)
Abstract Over the last two decades, the prevalence of myopia has gradually increased in China. Numerous epidemiological studies suggest that education and inadequate time spent outdoors are the major causes of the current myopia epidemic. China is one of the few countries that has begun to address the myopia epidemic with a national-level strategy, implementing nationwide education reform, cost-reduction measurements, and dissemination of information on myopia prevention and control. These “natural experiments” will provide insights into areas that may face similar or potential myopia problems.